TermosTeo: a elaboração de vocabulários monolíngues de termos da Teologia em um estudo conduzido por corpus - Cardoso, Solange Aparecida Faria (2017)
This work aims at the elaboration of three terminology vocabulary proposals in the Theology area that will use the Online Technical Vocabulary tool (VoTec) (FROMM, 2007), which can be viewed free of charge on an Internet page (votec.ileel.ufu.br). The theoretical foundings of this research are based on the theoretical and methodological concepts of the Communicative Theory of Terminology (TCT, CABRÉ, 1993; 1999); in dictionary, vocabulary and glossary conceptions of Barbosa (2001); in the studies of Barros (2004); Krieger and Finatto (2004) and Almeida et al. (2007) in relation to the elaboration of the definitions of the entries; in the theoretical assumptions for working with the methodology of Corpus Linguistics (BERBER SARDINHA, 2004; TEIXEIRA, 2008; SCOTT, 2012) and in the operation of the VoTec terminology management platform (FROMM, 2007). The textual corpora, which served to extract the terminological units and to the preparation of vocabulary proposals, were composed by written and digitized texts used by students, teachers and trainers in classes and evangelistic meetings of the Shalom College of Higher Education (Fases) and of the Catholic Faculty of Uberlândia (FCU). Our challenge was, by means of the texts that compose the corpora of this research, to list the terms and definitions that constitute the vision of the theological academic knowledge disseminated by Fases (Vocabulary of the terms of Theology – Fases) and by the Catholic Faculty of Uberlândia (Vocabulary of Terms of Theology – FCU). The third vocabulary (Vocabulary of terms in contrast) is the result of the confrontation between identical terms used in the two other vocabularies.